Proximal and distal impacts of a megaproject on ecosystem services in rural territories of the Yucatán Peninsula, Mexico - Zambrano, Luis; Fernandez Vargas, Tania; González, Edgar J.; Mendoza-Ponce, Alma; Vazquez Prada, Manuel Llano; Flores Lot, Carla; Corona-Nuñez, Rogelio O.; Martínez-Meyer, Enrique (Frontiers in Environmental Science, 2025)
IntroductionMegaprojects are strategically envisioned to boost regional development. Still, they drive ecosystem changes that generate ecological impacts in space and time beyond construction sites, particularly those established in rural regions, as their economic goals often trigger broader landuse changes. These distal ecological impacts are frequently overlooked, but their evaluation is critical to assess changes in ecosystem services that provide quality of life to the local people. To understand the effects on ecosystem services, this study analyzed both the proximal and distal impacts of the “Tren Maya” railroad megaproject.MethodsUsing InVest models, which provide spatial quantitative analysis using land use information, among other variables. We evaluated three ecosystem services: habitat quality, pollination, and carbon sequestration across the Yucatán Peninsula, Mexico. We assessed historical (2002) and recent (2017) ecosystem services. We projected three scenarios to 2050: (a) future without train, land use change using previous trends, (b) proximal impacts of the Tren Maya, and (c) combined proximal and distal impacts of the Tren Maya.ResultsResults show significant declines of all evaluated ecosystem services in the three future scenarios, with the most pronounced reductions with distal impacts. Ecosystem types have different impacts, where tropical rainforests and tropical dry forest are the most affected. Geographically, the northwestern region of the Peninsula (the most populated) is more affected, while protected areas in the southern region mitigate some impacts.DiscussionThe analysis shows that distal impacts are more significant in the habitat quality than the other two ecosystem services evaluated. Our findings underscore the need for megaproject evaluations to incorporate both proximal and distal impacts to ensure sustainable development.